Down syndrome with cryptorchidism and retroperitoneal mixed germ cell tumour in an adult patient: a case report and literature review - Qiang Wang; Hai-bin Zhou; Li Ao; Yi Jiang; Xiao-Cong Zhou (World Journal of Surgical Oncology)
Abstract Background An association between testicular cancer and Down syndrome has been reported by several studies. Down syndrome with cryptorchidism and retroperitoneal mixed germ cell tumours is rare, and yolk sac tumours are often considered secondary components of mixed germ cell tumours. Herein, we present a rare case of retroperitoneal mixed germ cell tumour with cryptorchidism accompanied by yolk sac tumour and seminoma in a patient with Down syndrome, along with its imaging features. Case presentation A 42-year-old man was admitted to the hospital for 6 months due to a worsening abdominal pain that was followed by syncope for 8 h. There was a significant increase in AFP and β-HCG levels. An enhanced computed tomography (CT) scan of the entire abdomen showed a mixed cystic solid mass in the retroperitoneal space. Fluorine-2-fluoro-2-deoxy-d-glucose (18F-FDG) positron emission tomography/CT examination showed an abnormal increase in the FDG uptake in the parenchymal part of the mass, with a maximum standardised uptake value of approximately 10.5. The pathological diagnosis was retroperitoneal mixed germ cell tumour (yolk sac tumour + seminoma). One and a half months postoperatively, the tumour recurred. Consequently, the patient underwent chemotherapy, and after one course of treatment, the patient developed bone marrow suppression. Finally, he died due to complications. Conclusions Yolk sac tumours, the main components of mixed germ cell tumours, are rare in adults and exhibit rapid growth, heightened malignancy, and poor prognoses. CT features play a crucial role in diagnosis. Down syndrome is a high-risk factor for malignant testicular germ cell tumours. Therefore, comprehensive examinations for gonadal and germ cell tumours in patients with Down syndrome are imperative and should be prioritised by clinicians.